Antibacterial Cu-doped cotton textile against respiratory pathogens for preventing hospital-acquired infections - Gao, Jianhui; Liu, Deliang; Lin, Zhiqiang; Zhou, Yang; He, Zhuojun; Dai, Xiafei; Zhao, Pengfei; Lu, Hongzhou; Zheng, Mingbin (Frontiers in Bioengineering and Biotechnology, 2025)
Respiratory pathogens transmitted via clinical textiles represent a major source of hospital-acquired infections, yet current antibacterial fabric strategies are limited by poor durability and weak bacterial inhibition. Here, we reported a molecular-level strategy for the fabrication of copper-doped antibacterial cotton textiles (Cu@textile) via a simple immersion of common cotton in a Cu(II)-saturated NaOH solution. This process enabled stable coordination between the copper ions and cellulose hydroxyl groups, forming stable Cu-O bonds throughout the fiber matrix. Structural and spectroscopic analyses confirmed uniform copper integration and chemical bonding. The resulting Cu@textile exhibited potent, broad-spectrum antibacterial activity against key respiratory pathogens, including Pseudomonas aeruginosa, Acinetobacter baumannii, and Mycobacterium tuberculosis, with >99% sterilization efficiency. Mechanistic studies revealed this efficacy as copper-induced reactive oxygen species (ROS) production and bacterial membrane disruption. This accessible and scalable antimicrobial textile eliminates the need for specialized equipment or nanoparticle synthesis, and may represent a strategic intervention to reduce bacteria propagation and contact infection risks in healthcare settings.